STRATEGI PEMASARAN TABUNGAN PADA BANK SUMUT SYARIAH DALAM MENINGKATKAN JUMLAH NASABAH BARU - Audri Fadillah Saputri; Ahmad Syakir (Jurnal Publikasi Manajemen Informatika, 2025)
This study aims to analyze the savings marketing strategy implemented by Bank Sumut Syariah Capem Marelan Raya in increasing the number of new customers. The research method used is qualitative with a field study approach. Data were collected through in-depth interviews with the Branch Manager and participatory observation. The results showed that Bank Sumut Syariah applies a marketing strategy based on the 7P marketing mix, which includes product, price, place, promotion, people, process, and physical evidence. Supporting factors for the success of this strategy include a trusted bank image, competitive products, and quality service. Meanwhile, the challenges faced include intense competition and a lack of public understanding of sharia finance. This research provides implications for Bank Sumut Syariah to continue innovating, optimizing digital technology, and increasing sharia financial literacy to increase the number of customers and strengthen its position in the market.